2019
DOI: 10.3390/app9173601
|View full text |Cite
|
Sign up to set email alerts
|

Study into the Improvement of Dynamic Stress Characteristics and Prototype Test of an Impeller Blade of an Axial-Flow Pump Based on Bidirectional Fluid–Structure Interaction

Abstract: This paper performed a numerical study into the dynamic stress improvement of an axial-flow pump and validated the simulation results with a prototype test. To further analyze the dynamic stress characteristics of impeller blades of axial-flow pumps, a bidirectional fluid–structure interaction (FSI) was applied to numerical simulations of the unsteady three-dimensional (3-D) flow field of the whole flow system of an axial-flow pump, and the gravity effect was also taken into account. In addition, real-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The finite element static stress calculation needs to impose sufficient constraints to restrain the movement of the structure and prevent the rigid displacement of the structure. 26 Because the cylindrical surface contacting the hub of the blade can only prevent the radial and axial movement of the blade, while the tangential direction can rotate, the cylindrical surface here is constrained by cylindrical constraints to restrict the radial and axial movement of the surface. The interface of fluid–solid coupling is the whole blade part.…”
Section: Methods Of Numerical Simulationmentioning
confidence: 99%
“…The finite element static stress calculation needs to impose sufficient constraints to restrain the movement of the structure and prevent the rigid displacement of the structure. 26 Because the cylindrical surface contacting the hub of the blade can only prevent the radial and axial movement of the blade, while the tangential direction can rotate, the cylindrical surface here is constrained by cylindrical constraints to restrict the radial and axial movement of the surface. The interface of fluid–solid coupling is the whole blade part.…”
Section: Methods Of Numerical Simulationmentioning
confidence: 99%
“…The flow inside the pump device is regarded as three-dimensional incompressible nonviscous turbulence. The control equation of numerical calculation is as (Shi et al, 2017;Chen et al, 2018;Kan et al, 2019):…”
Section: Governing Equationmentioning
confidence: 99%
“…Zhang et al [23] performed FSI calculations for a certain type of axial-flow pump, and the research shows that the natural frequency of the impeller is significantly reduced by the water medium, while the effect of prestress on the modal is not obvious. Kan et al [24,25] revealed the dynamic stress change law of the blade during the impeller design stage based on the FSI method and proposed that thickening the blade root can significantly improve the stress distribution of the blade and improve the safety and stability of the blade.…”
Section: Introductionmentioning
confidence: 99%